Influence of irrigation water intake on local increase of radiocesium activity concentration in rice plants near a water inlet. (December 2020) - Yoshikawa, Natsuki; Nakashima, Kosei; Suzuki, Yoshimasa; Miyazu, Susumu; Suzuki, Kazuki; Nogawa, Norio; Harada, Naoki
Abstract: To identify the cause of the phenomenon that rice plants close to the water inlet contain relatively higher radiocesium within a paddy field plot, we conducted a field experiment by establishing experimental channel using polypropylene corrugated sheets, and sampling surface water, paddy soil and rice plants according to the distance from the water inlet in 2014 and 2015. It was found that the 137 Cs activity concentrations in both dissolved and particulate forms in paddy surface water presented a declining trend from the water inlet towards the outlet. The 137 Cs activity concentration in paddy soil in the harvesting season and those of brown rice and rice straws were highest at 1–2 m from the water inlet. Balance calculation suggests that destination of the lost 137 Cs from the surface water was likely to be adsorption of the dissolved form and sedimentation of particulate form onto the soil. The concentration of exchangeable potassium ion in paddy soil was below the recommended standard of 250 mg kg −1 (as K2 O in dry soil) near the water inlet at the harvesting period both years．These findings suggested that the possible crucial factors to induce rice plant uptake of radiocesium near the water inlet were either (1) direct absorption of dissolved 137 Cs in surface water by rice plants, (2) absorption of 137 Cs, which was originally retained in particulate matter and released by ion exchange and/or by organic matter decomposition in combination with (3) loss of soil exchangeable potassium caused due partly to transportation of soil particles with exchangeable potassium by the rapid water flow near the water inlet and/or leaching by ion exchange onto the soil of other cations such as calcium ion flowing into the paddy field. These findings will contribute to providing possible measures for producing safe rice in highly contaminated areas in which agricultural production will resume in the near future. We propose providing a non-planting zone for the area closer than about 5 m from the water intake to avoid the occurrence of high 137 Cs concentrations in rice crops. Graphical abstract: Image 1 Highlights: Irrigation water intake causes radiocesium activity concentration increase in rice plants near the water inlet. Both dissolved and particulate radiocesium forms in surface water decreased from the inlet to the outlet. Likely causes of radiocesium losses from the surface water were adsorption and sedimentation onto the soil. The locally low exchangeable potassium concentration in soil was due to the quick flow near the inlet.